2015
DOI: 10.1021/acs.langmuir.5b00236
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Multimodal Ligands with Proteins: Insights into Selectivity Using Molecular Dynamics Simulations

Abstract: Fundamental understanding of protein-ligand interactions is important to the development of efficient bioseparations in multimodal chromatography. Here we employ molecular dynamics (MD) simulations to investigate the interactions of three different proteins--ubiquitin, cytochrome C, and α-chymotrypsinogen A, sampling a range of charge from +1e to +9e--with two multimodal chromatographic ligands containing similar chemical moieties--aromatic, carboxyl, and amide--in different structural arrangements. We use a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…In a recent paper we have reported that negatively charged multimodal cation exchange ligands—Capto MMC and Nuvia cPrime—interacted with positive and hydrophobic regions on the surfaces of proteins ubiquitin, cytochrome C and α‐chymotrypsinogen A. Further, it was shown that these ligands did not interact with negatively charged protein regions.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In a recent paper we have reported that negatively charged multimodal cation exchange ligands—Capto MMC and Nuvia cPrime—interacted with positive and hydrophobic regions on the surfaces of proteins ubiquitin, cytochrome C and α‐chymotrypsinogen A. Further, it was shown that these ligands did not interact with negatively charged protein regions.…”
Section: Resultsmentioning
confidence: 96%
“…All‐atom explicit–solvent MD simulations were performed to understand the binding of arginine and guanidine molecules to protein surfaces. Recent work in our group has focused extensively on the behavior of three model proteins—ubiquitin, cytochrome C, and α‐chymotrypsinogen A—in multimodal ligand systems . Since ubiquitin and cytochrome C exhibited decreased retentions in the presence of guanidine and α‐chymotrypsinogen A exhibited minimal change in retention, these proteins were selected as representatives of this proteins’ set for the first round of analysis using MD simulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yu et al employed coarse-grained simulations to investigate the preferred binding orientation of lysozyme on a HCIC surface at different ligand densities under a range of salt concentrations (Yu, Liu, & Zhou, 2015). Our lab has been actively involved in studying the preferred binding regions of small proteins in MM CEX systems by employing protein libraries (Chung, Hou, et al, 2010), MD simulations Freed, Garde, & Cramer, 2011;Parimal, Garde, & Cramer, 2015, 2017, Atomic Force Microscopy (AFM) (Srinivasan et al, 2017) and Nuclear Magnetic Resonance (NMR) Holstein, Chung, et al, 2012;Holstein, Parimal, McCallum, & Cramer, 2013;Srinivasan, Parimal, Lopez, McCallum, & Cramer, 2014).…”
Section: Introductionmentioning
confidence: 99%